Association between DEFB103 gene copy number variation and ankylosing spondylitis: a case–control study. Issue 3 (30th July 2015) - Cai, G.; Xia, Q.; Fan, D.; Li, X.; Ding, N.; Hu, Y.; Yang, X.; Liu, L.; Xin, L.; Wang, L.; Xu, S.; Xu, J.; et al.
Abstract In this brief communication, we investigate the role of DEFB103 gene copy number variation (CNV) in ankylosing spondylitis (AS) susceptibility. A total of 807 Chinese individuals including 406 AS patients and 401 controls were enrolled. The DEFB103 copy number was measured by two sets of probes to obtain a stable result in a custom‐by‐design Multiplex AccuCopy™ kit (Genesky Biotechnologies Inc., Shanghai, China) based on a multiplex fluorescence competitive polymerase chain reaction (PCR) principle. The copy number of DEFB103 ranged from 2 to 6 in both AS patients and controls. Mann–Whitney U test and chi‐squared test were performed to analyze the difference of DEFB103 copy number between AS patients and controls while no statistical difference has been found. We considered the copy number of DEFB103 gene may not associate with susceptibility to AS.